1988
DOI: 10.1152/jappl.1988.65.5.1957
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cardiac response to isoproterenol infusion in acute and chronic hypoxia

Abstract: The hypothesis of a blunted chronotropic response of cardiac beta-adrenergic receptors in altitude hypoxia was tested in nine subjects at sea level (SL) by infusion of isoproterenol. Observations were made at SL, in acute hypoxia (2 days at 4,350 m, condition H1), in more prolonged hypoxia [13 days between 850 and 4,800 m, condition H2] and in chronic hypoxia [21 days at 4,800 m, condition H3]. Resting heart rate was higher in all hypoxic conditions. Resting norepinephrine concentrations were found to be signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 0 publications
6
43
0
Order By: Relevance
“…Conflict surrounds the interpretation of the effect of the HR peak modification in hypoxia on _ V O 2max . According to the Fick equation _ V O 2 =HRAESV(Cao 2 -Cvo 2 ), it has been postulated that the alteration in DHR peak and SaO 2 would modify _ V O 2max (Richalet et al 1988). Gonzalez et al (1998) demonstrated that an increase in HR peak by atrial pacing induced an increase both in maximal cardiac output and _ V O 2max in hypoxia.…”
Section: Hr Peak Decrement In Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…Conflict surrounds the interpretation of the effect of the HR peak modification in hypoxia on _ V O 2max . According to the Fick equation _ V O 2 =HRAESV(Cao 2 -Cvo 2 ), it has been postulated that the alteration in DHR peak and SaO 2 would modify _ V O 2max (Richalet et al 1988). Gonzalez et al (1998) demonstrated that an increase in HR peak by atrial pacing induced an increase both in maximal cardiac output and _ V O 2max in hypoxia.…”
Section: Hr Peak Decrement In Hypoxiamentioning
confidence: 99%
“…Decreased maximal heart rate (HR peak ) is well established in subjects acclimatized to high altitude (Pugh 1964;Reeves et al 1987;Richalet et al 1988). This lower HR peak is linked to the severity and the duration of the hypoxemia (Savard et al 1995) and contributes to the decrease in maximal oxygen uptake ( _ V O 2max ) observed when these subjects are exposed to chronic hypoxia (Richalet et al 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norepinephrine and epinephrine levels have been observed not to change (Bouissou et al 1989;Mazzeo et al 1995;Richalet et al 1988), decrease (Rostrup 1998) or increase (Bartsch et al 1991;Mazzeo et al 1995) during acute hypobaric hypoxic exposure. We observed a significant increase in both norepinephrine and epinephrine levels following rapid ascent to altitude.…”
Section: Discussionmentioning
confidence: 93%
“…Another factor, which has been demonstrated to aVect the activity in autonomic nervous system, is exposure to hypoxia (Richalet et al 1988). During acute hypoxic exposure, a general decrease in cardiac autonomic nervous function has usually been reported as reXected in a decrease of HRV, and a dominance of sympathetic over the parasympathetic modulation has been observed (Hughson et al 1994;Farinelli et al 1994;Perini et al 1996;Kanai et al 2001).…”
Section: Introductionmentioning
confidence: 99%